Lianas Significantly Reduce Aboveground and Belowground Carbon Storage: A Virtual Removal Experiment - Meunier, Félicien; van der Heijden, Geertje M. F.; Schnitzer, Stefan A.; De Deurwaerder, Hannes P. T.; Verbeeck, Hans (Frontiers in Forests and Global Change, 2021)
Lianas are structural parasites of trees that cause a reduction in tree growth and an increase in tree mortality. Thereby, lianas negatively impact forest carbon storage as evidenced by liana removal experiments. In this proof-of-concept study, we calibrated the Ecosystem Demography model (ED2) using three years of observations of net aboveground biomass changes in control and removal plots of a liana removal experiment on Gigante Peninsula, Panama. After calibration, the model could accurately reproduce the observations of net biomass changes, the discrepancies between treatments, as well as the observed components of those changes (mortality, productivity, and growth). Simulations revealed that the long-term total (i.e. above- and belowground) carbon storage was enhanced in liana removal plots (+ 1.2 kgC m-2 after 3 years, + 1.8 kgC m-2 after 10 years, as compared to the control plots). This difference was driven by a sharp increase in biomass of early successional trees and the slow decomposition of liana woody tissues in the removal plots. Moreover, liana removal significantly reduced the simulated heterotrophic respiration (-24%), which resulted in an average increase in net ecosystem productivity from 0.009 to 0.075 kgC m-2 yr-1 for ten years after liana removal. Based on the ED2 model outputs, lianas reduced gross and net primary productivity of trees by 40% and 53%, respectively, mainly through competition for light. Finally, model simulations suggested a profound impact of the liana removal on the soil carbon dynamics: the simulated metabolic litter carbon pool was systematically larger in control plots (+51% on average) as a result of higher mortality rates and faster leaf and root turnover rates. By overcoming the challenge of including lianas and depicting their effect on forest ecosystems, the calibrated version of the liana plant functional type as incorporated in ED2 can predict the impact of liana removal at large-scale and its potential effect on long-term ecosystem carbon storage.